Can cheetahs and wildlife ranchers ever live in co-existence? - Marker, Laurie, author; International Wildlife Ranching Symposium, publisher (Colorado State University. Libraries, 2016)
Large carnivores are currently facing severe threats and are experiencing substantial declines in their populations and geographical ranges around the world (Ripple et al., 2014). Human-wildlife conflict is a risk to 31% of the global carnivore species (IUCN Red List, 2016). The vast majority of Namibia's cheetahs (Acinonyx jubatus) (over 90%) and other large carnivores reside outside of national parks. Namibia is made up of a mosaic of land uses which includes both privately owned mixed livestock and wildlife unfenced farms, fenced game farms, and open communal and commercial conservancies. Fences are meant to protect biodiversity however; fences have an ecological impact by blocking migration movements especially in arid ecosystems. The fences confine individuals in turn carnivore abundance may exceed their available resources leading to a potential rapid decline of the population or local extinction. Commercial farmers have utilised game fences to keep and protected their game which equates to their livelihood. However, game fenced farmers catch more cheetahs than that of livestock farmers (Marker et al. 2010). As more game fences are erected, the rate of human-wildlife conflict has increased, which is an issue not only for the cheetah but all large carnivores across Namibia. CCF's research over the years has uncovered the complex relationships between individual cheetahs, their competition such as leopards and their prey base. By understanding these relationships it is possible to share information on how these influences affect cheetahs on game ranching farms and in turn how farmers can farm in co-existence. CCF's Future Farmers of Africa (FFA) project is a multifaceted integrated programme as it aims to help farmers with both human and environmental issues through education. CCF has created a set of integrated programmes aimed at addressing the principle threats to the cheetah by developing simple techniques through their FFA's programme and farmer training workshops. These tools include; livestock guarding dogs and swing gates that allow free movement of animals across game farms. These tools have already reduced the rate of human-wildlife conflict and help to maintain a viable population of carnivores across Namibia's conservancies. Through education CCF believes that both commercial and communal farmers can successfully live together with large carnivores across Namibia now and in the future.
Presented at the 9th international wildlife ranching symposium: wildlife - the key to prosperity for rural communities, held on 12-16 September 2016 at Hotel Safari & the Safari Court, Windhoek, Namibia.